2022
DOI: 10.3389/fneur.2022.616964
|View full text |Cite
|
Sign up to set email alerts
|

Free-Breathing, Non-Gated Heart-To-Brain CTA in Acute Ischemic Stroke: A Feasibility Study on Dual-Source CT

Abstract: PurposeTo validate the feasibility of free-breathing, non-gated, high-pitch heart-to-brain computed tomography arteriography (CTA) in acute ischemic stroke and the capability of non-gated heart-to-brain CTA in showing cardiac anatomy.Materials and MethodsThe study protocol was approved by the institutional medical ethics review board. Free-breathing, non-gated, high-pitch heart-to-brain CTA was performed on patients with acute ischemic stroke referred for multimodal CT using a third-generation dual-source CT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Nevertheless, for carotid and cerebrovascular vessels, we have to admit that the image quality was not significantly improved using DLIR-H under the lower-dose conditions. Similarly, all the former one-stop C&CC-CTA protocols reported comparable or even worse image quality at the same site ( 12 , 14 , 15 ). We speculate that it might be attributed to the order of scanning, as the carotid and cerebrovascular arteries were always scanned behind coronary arteries in the one-stop scanning process.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Nevertheless, for carotid and cerebrovascular vessels, we have to admit that the image quality was not significantly improved using DLIR-H under the lower-dose conditions. Similarly, all the former one-stop C&CC-CTA protocols reported comparable or even worse image quality at the same site ( 12 , 14 , 15 ). We speculate that it might be attributed to the order of scanning, as the carotid and cerebrovascular arteries were always scanned behind coronary arteries in the one-stop scanning process.…”
Section: Discussionmentioning
confidence: 84%
“…Repeated examination for different sites will also increase the treatment expense. Recently, one-stop coronary and carotid-cerebrovascular CTA (C&CC-CTA) protocol using iterative reconstruction (IR) algorithm has been introduced and provides a potential clinically feasible examination for patients suspected with co-existing atherosclerosis disease ( 12 - 17 ). However, previously published one-stop C&CC-CTA protocols still presented with slightly high image noise, and the radiation and contrast dose are expected to be further reduced.…”
Section: Introductionmentioning
confidence: 99%
“…When the heart was scanned by CTA, many different tissues were involved, including the heart, bone, lung, and coronary artery [ 17 , 18 ]. Different tissue densities were generated.…”
Section: Methodsmentioning
confidence: 99%
“…Different techniques are available for screening heart using CT in stroke patients including the use of different gating techniques 9 and with single or dual energy 10 methods as follows: Retrospective electrocardiogram (ECG)-gated cardiac screening Non-ECG-gated extended Z-axis coverage cardiac screening Prospective-gated cardiac screening …”
Section: Multiphasic Ctamentioning
confidence: 99%
“…Dual energy scanners have shown that even a free-breathing, non-gated, and high-pitch heart-to-brain CTA protocol can be incorporated in the multimodal CT of AIS without significant differences in image quality, or an increase of radiation dose in comparison to the breath-hold ECG-gated CTA. 9, 10 While extending the Z-axis without gating carries the least radiation dosage, image quality for diagnostic purposes is poorer than the other methods. Dual energy retrospective gating carries highest radiation with the best imaging quality.…”
Section: Cardiac Gatingmentioning
confidence: 99%